ANALISIS KLASTER MENGGUNAKAN METODE HIERARKI UNTUK PENGELOMPOKKAN PENGELUARAN PERKAPITA RUMAH TANGGA DI SUMATERA UTARA - Raidhatul Ilmi; Machrani Adi Putri Siregar; Silvia Harleni (LPPM Universitas Bina Bangsa, 2023)
Capita household expenditure is the cost incurred for the consumption of all family members for a month divided by the number of family members adjusted for purchasing power parity. It is necessary to pay attention to the factors that affect the level of household expenditure. Several factors that affect household expenditure are divided into two parts, namely food and non-food expenditure. Household expenditure in each region has different characteristics, therefore it is necessary to group regions so that solutions can be implemented according to each region's characteristics. The purpose of this research is to classify districts/cities in North Sumatra based on the factors that influence per capita household spending in each region using cluster analysis based on the single linkage and complete linkage methods. Cluster analysis is grouping into clusters so that the objects in the cluster are more similar to one another than the objects in other clusters. From the results of cluster analysis using the single linkage and complete linkage methods, it shows that there are four Regency/City groups that are combined based on each factor that influences household per capita expenditure